Quercetin ameliorates inflammation in CA1 hippocampal region in aged triple transgenic Alzheimer´s disease mice model (2018)
ABSTRACT: Alzheimer’s disease is the most common form of dementia. It is characterized by histopathological hallmarks such as senile plaques and neurofibrillary tangles, as well as a concomitant activation of microglial cells and astrocytes that release pro-inflammatory mediators such as IL-1β, iNOS, and COX-2, leading to neuronal dysfunction and death.